Optimization of the tactical thought starting from simplified games of soccer in sport initiation. - Corcho Busto, H.M.; González Padrón, C.Á.; Arrojo Sureda, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
This research answers to the limited actions in the Integral Program of Preparation of the Sportsman of the soccer for the development of the tactical thought, related to the scientific problem: How to contribute to the stimulation of the soccer player tactical thought in the sport initiation? The purpose is: to design simplified soccer games to stimulate the soccer player tactical thought in the sport initiation. With this purpose, 16 male soccer players aged 10 to 13 years, were administered 2 tests to evaluate the state of the operative thought. A series of simplified games is selected and they are applied by means of a pre experiment. After the application of the simplified games, the soccer players use the technical elements through the dialogue with their coach and they are capable to understand the positive and negative actions in tactical game situations.